Weight and height percentiles calculated by the LMS method in Argentinean schoolchildren. A comparative references study - Oyhenart, Evelia E.; Lomaglio, Delia B.; Dahinten, Silvia L. V.; Bejarano, Ignacio F.; Herráez, Ángel; Cesani, María F.; Torres, María F.; Luis, María A.; Quintero, Fabián A.; Alfaro, Emma L.; Orden, Alicia B.; Bergel Sanchis, María L.; et al. (Annals of human biology, 2015)
Background: The Argentinean population is characterized by ethnic, cultural and socio-economic diversity. Aim: To calculate the percentiles of weight-for-age (W/A) and height-for-age (H/A) of schoolchildren from Argentina employing the LMS method; and to compare the obtained percentiles with those of the international and national references. Subjects and methods: Anthropometric data of 18 698 students (8672 girls and 10 026 boys) of 3-13 years old were collected (2003-2008) from Buenos Aires, Catamarca, Chubut, Jujuy, La Pampa and Mendoza. Percentiles of W/A and H/A were obtained with the LMS method. Statistical and graphical comparisons were established with the WHO (international reference) and with that published by the Argentinean Paediatric Society (national reference). Results: Differences in W/A and H/A, regarding the references, were negative and greater at the highest percentiles and in most of the age groups. On average, the differences were greater for boys than girls and for national than international references. Conclusion: The distribution of weight and height of schoolchildren, coming from most regions of the country, differs from those of national and international references. It should be advisable to establish a new national reference based on internationally recognized methodological criteria that adequately reflect the biological and cultural diversity of the Argentinean populations.